Pengembangan Media Komik Digital Interaktif: “Daerahku dan Kekayaan Alamnya” dengan Pendekatan Berdiferensiasi - Lintang Kirana Leokiss Wijaya; Barokah Isdaryanti (Postgraduate, University of Mataram, 2025)
This study addresses the scarcity of technology-based learning media for natural and social sciences learning tailored to the diverse learning needs of fourth-grade students in Semarang, particularly in regards to regional natural resource potential. The primary objective is to design, evaluate the feasibility, and assess the effectiveness of Interactive Digital Comic media with a differentiated approach. This development research uses the Research and Development (R&D) method with the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation phases. The feasibility assessment by material experts and media experts yielded a percentage of 92.85% and 87.50%, respectively, rating the media as